Interpretasi Tingkat Kekerasan Batuan Bawah Permukaan di Daerah Rawan Gempa Bumi Kota Bengkulu - Arif Ismul Hadi; Refrizon Refrizon; Halauddin Halauddin; Liza Lidiawati; Paisal Edo (Department of Physics, Sebelas Maret University, 2021)
Bengkulu City is located in the subduction zone of the Indo-Australian and Eurasian plates, so it is prone to earthquake. To anticipate the impact of earthquake, disaster mitigation can be carried out, one of which is a study of the level of rock hardness in the area. This study aims to determine the level of rock hardness based on seismic wave velocity in several rock formations and to determine which rock formations have the potential to cause vulnerability to earthquakes. Field data acquisition uses the seismic refraction method with time-term inversion technique. The data obtained in the field are processed to obtain a 2-D cross-section of the subsurface seismic wave velocity values. The study results show that the level of rock hardness depends on the type of rock formation. The Andesite Rock Formation Unit (Tpan) has the highest level of hardness, while the transitional area between the Alluvium Rock Formation Unit (Qa) and the Swamp Sedimentary Rock Formation Unit (Qs) has the lowest level of hardness.